(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study the basic elements that lead to success of leadership by love through the study of dimensions that contributes to achieve leadership by love related to the conduct of leader behavior towards dealings with subordinates from all psychological, accepting social, emotional, appreciating, spiritual and philosophical aspects of the subordinates , love, affection, respect, being Altruistic, being Open, giving, growing, valuing ,and trust and relationship between the leader and subordinates to achieve the goals of the organization and subordinates and thus reflect positively on the success of the organization and its development ,also increasing the productivity of workers and job satisfaction, leadership by love aims to feel the social responsibility towards society, country , citizen and customer . The study, through studying the results of previous research and theoretical literature, reached a set of results, which was that leadership by love plays a major role in increasing the productivity of workers and achieving psychological and employment satisfaction for subordinates more than material incentives such as respect subordinates, solve their psychological, social problems, involve them in decision-making, planning and setting goals. Also achieving mutual trust between the leader and subordinates, as well as the participation of workers in social and personal interests, love, affection, respect, being Altruistic, being Open, giving, growing, valuing, Considerate in social, cultural, religious and ethnic values, and paying attention to subcultures. The researcher recommends paying attention to leadership with love, because it is beneficial for the leader, followers, organization and the community